An analysis of gamification elements in mHealth applications - Rocha, Ivan; Silveira, Milene Selbach (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
In recent years, there has been an increase in the adoption of smartphones, by health professionals and the general public, for issues related to well-being and physical and mental health. This is related to electronic health and involves the use of mobile health (mHealth), which are health practices that use mobile devices. To increase usage and keep the user engaged in these practices, gamification started to be used by mHealth researchers and developers. Given this scenario, the main goal of this work is to analyze which gamification elements have been commonly applied to promote health and well-being in mHealth applications. For this, an analysis of mHealth applications present in the Google Play Store was carried out. With the analysis performed, 70 mHealth gamified applications were found. As a result, we identified which areas mHealth is typically found in and which gamification elements are most commonly found in them. It is expected that the results of this work will help mHealth researchers to understand the use of gamification elements better.